Peningkatan Pendapatan Keluarga Melalui Produksi Kecap Limbah Tahu - Astuty, Yoni; Rahayu, Lestari; Suryani, Lilis (Universitas Muhammadiyah Yogyakarta, 2018)
Tofu is made of soybean. Tofu is one of the protein sources needed by our body. During the process of making tofu is produced waste materials (waste) both with a solid texture or liquid. Solid texture waste is usually sell very cheap for livestock feed, whereas liquid waste is thrown away with other domestic wastes every day. The liquid waste volume was increasing daily. People was produce tofu everyday so it is definitely waste formed daily that is dis-charged to the environment. It is feared can further pollute the environment. The purpose of this community service is to utilize the tofu waste as the raw material for soy sauce in an effort to overcome environmental pollution by tofu industry waste and increase the family income. The methods used in this community service were counseling, training and skills practices of targeted community groups on the mastery of processed waste technologies in the form of soy sauce. Also to facilitate some tools to support tofu production process. The result of community service shows that the target community has been able to master the processing of tofu waste into soy sauce from the beginning of processing until the production, soy sauce produced has been marketed and generated a profit of 4.5%. And the profit that can be obtained in soy sauce production is 4.5%. Key words : Tofu waste, Soy sauce, Environment pollution, income